Timing of BNT162b2 vaccine prior to COVID‐19 infection, influence disease severity in patients with hematologic malignancies: Results from a cohort study - Odit Gutwein; Katrin Herzog Tzarfati; Arie Apel; Naomi Rahimi‐Levene; Levy Ilana; Tamar Tadmor; Maya Koren‐Michowitz (Cancer Medicine, 2023)
Abstract The COVID‐19 pandemic continues to pose challenges to the treatment of hemato‐oncology patients. Emergence of COVID‐19 variants, availability of vaccine boosters and antiviral treatments could impact their outcome. We retrospectively studied patients with hematologic malignancies and confirmed COVID‐19 during the Omicron outbreak. Of 116 evaluated patients, 16% developed severe or critical COVID‐19. Diagnosis of chronic lymphocytic leukemia (CLL) was significantly associated with severe COVID‐19 (p = 0.01). The vaccine effectiveness was related to the timing of the vaccine, with patients who received a mRNA vaccine within 7–90 days prior to COVID‐19 being less likely to develop severe disease compared to all other patients (p = 0.019). There was no correlation between disease severity and antiviral therapies. Importantly, 45% of patients undergoing active hematological treatment had to interrupt their treatment due to COVID‐19. In conclusion, patients with hematologic malignancies are at a considerable risk for severe COVID‐19 during the Omicron outbreak, with patients with CLL being the most vulnerable. mRNA vaccines have the potential to protect hematological patients from severe COVID‐19 if administered within the previous 3 months. Hematological treatment interruption is a frequent adverse outcome of COVID‐19 infection.